Perceptions in Play: English Students on Using Music Video to Write Narrative Text - Endra Kurniawan, Deny; Aimah, Siti; Darwis, Djamaluddin (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
This research explores the perceptions of English students about using the music video to influence their writing in narrative text. This research employed quantitative research methods, using questionnaires and interviews as the instruments to collect the data. The participants of this research were English students that consisted of two majors, including 17 English education students and 13 English literature students in the fourth semester. The data was analyzed using quantitative methods. The questionnaire tool uses Google Forms. The results showed that there were positive reasons for the students' perspective on learning using music videos when they wrote their narrative text. The music video helps them to find ideas in the brainstorming and All in all, the students had to focus and create comfortable environments when they did the writing process with the use of music videos to motivate their creative writing on the narrative text.